ANALISIS PENGARUH PRODUK DOMESTIK REGIONAL BRUTO, JUMLAH PENDUDUK, JUMLAH PERUSAHAAN DAN INVESTASI TERHADAP PENDAPATAN ASLI DAERAH (Studi Kasus pada Kabupaten/Kota di Provinsi Jawa Tengah) - Djoko Kristianto, Wiji Lestari, Suharno & (Universitas Slamet Riyadi, 2017)
Each local government is vying to be able to improve own economic recovery,including improving revenue (PAD). The larger the PAD then it shows that theregion is able to implement fiscal decentralization and reduced dependence on thecentral government. The purpose of this study was to analyze the significance of theinfluence of the GDP, population, number of firms and investment simultaneously onrevenue to the district / city in Central Java province in 2010-2014. This study uses acase study at the district / city in Central Java province, the type of data usedquantitative and qualitative data, the data source used secondary data. Populationand sample in this research is all regencies / cities in Central Java province a totalof 35 districts / cities, so this study is a census study. Data analysis techniques usedclassical assumption test and multiple linear regression analysis. In conclusion that:the GDP significantly and negatively related to source revenue at district / town inCentral Java. The population, the number of companies and investments are notsignificant positive effect on revenue in the regency / city in Central Java. Theinfluence of the GDP, population, number of firms and investment simultaneouslysignificant effect on the dependent variable is the local revenue in regencies / citiesin Central Java.Keywords: The GDP, population, number of enterprises, investment, revenue.